Effect of Ultrasound Versus Transcutaneous Electrical Nerve Stimulation in Management of Carpal Tunnel Syndrome - Bhavani Prathap, Suganthirababu; Vinodhkumar, Ramalingam; Vignesh, Srinivasan; Kumaresan, Abathsagayam; Jagatheesan, Alagesan (INTI International University, 2023)
Background: Carpal tunnel syndrome (CTS) is the second most prevalent cause of work absence, resulting in hand functional loss and disability which affects 5.8% in women and 0.6% in men. This compression neuropathic syndrome causes pain, numbness& paraesthesia in the median nerve's distribution. Atrophy of thenar muscles may occur in later stage. Objective: The purpose of the study is to evaluate the effects of ULTRASOUND and TENS in the management of CTS. Methodology: A total of 30 subjects with CTS were selected according to inclusion and exclusion standards. Patients were split into two groups at random (experimental -15, conventional-15). The experimental group will receive ULTRASOUND along with wrist mobility exercise. The conventional group will receive TENS along with wrist mobility exercise for the period of two sets of five reps, five times per week for six weeks. VAS pain scale and BCTQ (Boston carpal tunnel questionnaires) was utilized as an outcome measure. Result: The mean value of pretest was (VAS-5.13, SSS-29.27, FSS-19.93) and the posttest values was (VAS-2.00, SSS-14.07, FSS-9.13) for experimental group and the mean value of pretest was (VAS-5.20, SSS-29.67, FSS-20.73) and the post values was (VAS-4.00, SSS-21.52, FSS-16.93) for conventional group, respectively. Conclusion: From the study, it has been concluded that ULTRASOUND showed the better results in pain relief and functional activity in patients with CTS. Although TENS showed gradual improvement in pain relief alone.